(untitled) - Hromadka, Martin (Doprava a spoje, 2012)
This paper discusses the relation between both wind speed and direction and low cloud base height at Bratislava airport. The data collection carried out during 10 year period. Data analyses conducted within this paper is a part of the project ``Centre of Excellence for Air Transport'' ITMS 26220120065.